1993
DOI: 10.1128/jvi.67.8.4549-4556.1993
|View full text |Cite
|
Sign up to set email alerts
|

African swine fever virus encodes a serine protein kinase which is packaged into virions

Abstract: Nucleotide sequencing of the SalI j region of the virulent Malawi (LIL20/1) strain ofAfrican swine fever virus (ASFV) identified an open reading frame (ORF), designated j9L, with extensive similarity to the family of protein kinases. This ORF encodes a 35.1-kDa protein of 299 amino acids which shares 24.6% amino acid identity with the human pim-1 proto-oncogene and 21.0%6 identity with the vaccinia virus BlR-encoded protein kinase. The ASFV ORF contains the motifs characteristic of serine-threonine protein kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…This region differed from the consensus in AoGV. However, inconsistencies are shown in this region in PxGV and XcGV (Hayakawa et al ., 1999 ) and in protein kinases from other organisms (Russell & Nurse, 1987 ; Baylis et al ., 1993 ). The consensus motif X is absent in AoGV but is also poorly conserved in other baculovirus proteins.…”
Section: Resultsmentioning
confidence: 99%
“…This region differed from the consensus in AoGV. However, inconsistencies are shown in this region in PxGV and XcGV (Hayakawa et al ., 1999 ) and in protein kinases from other organisms (Russell & Nurse, 1987 ; Baylis et al ., 1993 ). The consensus motif X is absent in AoGV but is also poorly conserved in other baculovirus proteins.…”
Section: Resultsmentioning
confidence: 99%
“…There are two different DNA polymerase mutations found among these strains. The single UL97 mutation is significant in that it occurs within a region of the gene that contains conserved residues shared by a large number of cellular and viral protein kinases as well as a number of bacterial phosphotransferases (2,5,7,10,13,15,16,34). This corresponds to region VI defined by Hanks et al (13).…”
Section: Discussionmentioning
confidence: 99%
“…The vaccinia virus BlR product is a serine/threonine kinase and is found in the virion (18). African swine fever virus encodes a kinase which phosphorylates serine and also appears to be a virion protein (2).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of numerous cellular and viral proteins is also observed in virally infected cells, which suggests that the protein kinases may have a role in regulating a wide variety of viral infections (Leader and Katan, 1988;Burma et al, 1994;Guarino et al, 1992;Kann et al, 1999). Protein phosphorylation in virally infected cells may depend on cellular protein kinases (Prives, 1990) or virally encoded protein kinases (for examples, see Smith and Smith, 1989;Wu et al, 1990;Zhang et al, 1990; Barik and Banerjee, 1992;Lin et al, 1992;Baylis et al, 1993;Bischoff and Slavicek, 1994;Reilly and Guarino, 1994;Li and Miller, 1995). These virally encoded protein kinases possess most, if not all, of the conserved motifs (subdomains I-IX as defined by Hanks et al, 1988) of the catalytic domains found in eukaryotic protein kinases.…”
Section: Introductionmentioning
confidence: 99%